Nanocomposites Recent Evolutions - Sivasankaran, Subbarayan (IntechOpen, 2019)
To have unimaginably outstanding useful properties (physical, mechanical, electrical, optical, chemical, and magnetic) in a single material design is a highly challenging task in the material science community, which can be achieved through nanocomposites. These nanocomposites can be produced from all conventional materials, which include polymers, metals/alloys, and ceramics, by modifying their internal structures. Due to modification of the structures of all kinds of conventional materials, at either the nano or ultra-fine level, the materials exhibit superior performance, which is a boon for all fields of science. In general, nanocomposite materials can be manufactured by solid-state processing techniques, liquid metallurgy, ex-situ and in-situ powder metallurgy, and other basic science synthesis routes. Furthermore, the possibility of making environmentally friendly materials is also possible with nanotechnology. Therefore, to investigate and demonstrate developments in the field of nanocomposites, this book is targeted at all the scientific personnel working in this field.